PUBI perceptions, attitudes and Expfctations toward nurses' competence in Johor - Rui, Wong Yu (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2012)
Competence is a complex multidimensional phenomenon. Nurses demonstrate competence nursing care that leads to patients· perspective of care and satisfaction. Nurses· competency is substantially very important -to ensure the quality of care giving to the patient. The aim of thjs study was to determine the public perception. attitudes= and expectation towards nurses' competence in the provision of nursing care in Johor. A cross sectional survey on public (n = 154) in Johar was done us ing a selfadministered Slrnctured questionnaire. Data was analyzed using the Statistical Package Social Science (SPSS) software version 18.0. From the finding. there is a s lightly positive perception and attitude from the public towards nurses' competencies in Johor. The public also shows high expectations towards nursing competencies. Besides. this study highlighted that the older participant score higher in the attitudes towards nurses· competence compared with the younger respondents. While the lower educated group show higher expectation towards nurses' competence. Regarding ethnicity, Indians have highest expectation towards nurses· competencies. fol lowed by Malay. \Vhile Chinese has lesser expectation towards nurses' competencies. Using Pearson correlation. researcher found that there was a significant association between public·s attitudes and their perception towards nurses' competencies. There was also a significant finding that there was an association between public's perceptions and their expectations towards nurses· competencies in Johor. This study provided the bas is for further research on public perception. attitudes, and expectations towards nurses' competencies.